Fresno County Legal Services Office Reception - Watkins, Howard::::::::: (1978)
Howard Watkins presenting NLADA Medallions to Fresno Bee reporters Erik Strom and William Patterson; photo by Ryan Marty. Member Fresno Bee 4 honored w/Emery Brommell Press Award